A Cobalt(I) Pincer Complex with an η2‐Caryl−H Agostic Bond: Facile C−H Bond Cleavage through Deprotonation, Radical Abstraction, and Oxidative Addition. (28th January 2016) - Murugesan, Sathiyamoorthy; Stöger, Berthold; Pittenauer, Ernst; Allmaier, Günter; Veiros, Luis F.; Kirchner, Karl
Abstract: The synthesis and reactivity of a Co I pincer complex [Co( ϰ 3 P, CH, P ‐P(CH)P NMe ‐ i Pr)(CO)2 ] + featuring an η 2 ‐ Caryl −H agostic bond is described. This complex was obtained by protonation of the Co I complex [Co(PCP NMe ‐ i Pr)(CO)2 ]. The Co III hydride complex [Co(PCP NMe ‐ i Pr)(CN t Bu)2 (H)] + was obtained upon protonation of [Co(PCP NMe ‐ i Pr)(CN t Bu)2 ]. Three ways to cleave the agostic C−H bond are presented. First, owing to the acidity of the agostic proton, treatment with pyridine results in facile deprotonation (C−H bond cleavage) and reformation of [Co(PCP NMe ‐ i Pr)(CO)2 ]. Second, C−H bond cleavage is achieved upon exposure of [Co( ϰ 3 P, CH, P ‐P(CH)P NMe ‐ i Pr)(CO)2 ] + to oxygen or TEMPO to yield the paramagnetic Co II PCP complex [Co(PCP NMe ‐ i Pr)(CO)2 ] + . Finally, replacement of one CO ligand in [Co( ϰ 3 P, CH, P ‐P(CH)P NMe ‐ i Pr)(CO)2 ] + by CN t Bu promotes the rapid oxidative addition of the agostic η 2 ‐Caryl −H bond to give two isomeric hydride complexes of the type [Co(PCP NMe ‐ i Pr)(CN t Bu)(CO)(H)] + .